2004
DOI: 10.1074/jbc.m313410200
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into Arginine Degradation by Arginine Deiminase, an Antibacterial and Parasite Drug Target

Abstract: L-Arginine deiminase (ADI) catalyzes the irreversible hydrolysis of arginine to citrulline and ammonia. ADI is involved in the first step of the most widespread anaerobic route of arginine degradation. ADI, missing in high eukaryotes, is a potential antimicrobial and antiparasitic drug target. We have determined the crystal structure of ADI from Pseudomonas aeruginosa by the multiwavelength anomalous diffraction method at 2.45 Å resolution. The structure exhibits similarity to other arginine-modifying or subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
100
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 30 publications
4
100
0
Order By: Relevance
“…In agreement with its predicted role as a nucleophile attacking the carbon of the guanidinium moiety, mutation of Cys 365 to serine severely compromised the activity of the enzyme. These observations indicate that AstB uses a catalytic mechanism similar to those of amidinotransferases and deiminases (30,31,36).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…In agreement with its predicted role as a nucleophile attacking the carbon of the guanidinium moiety, mutation of Cys 365 to serine severely compromised the activity of the enzyme. These observations indicate that AstB uses a catalytic mechanism similar to those of amidinotransferases and deiminases (30,31,36).…”
Section: Resultsmentioning
confidence: 85%
“…Detailed catalytic mechanisms have been proposed for the arginine deaminases (30,31). Surprisingly, comparison of the side chains in the vicinity of the guanidinium moiety of ADI (Protein Data Bank code 1LXY (30)) and AstB shows nearly identical environments (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatographic materials, buffers, 2-benzyl-2-thiopseudourea, L-arginine, L-citrulline, and agmatine were purchased from Sigma, molecular biological materials were from Invitrogen, [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]-L-arginine (specific activity ) 50 mCi/mmol) was from Moravek Biochemicals, Inc., N ω -amino-L-arginine was from Alexis Biochemicals, and N ω -methyl-L-arginine was from Bachem California Inc. N-Amino-L-citrulline (12) was obtained as a gift from Dr. Bruce King at Wake Forest University.…”
Section: Methodsmentioning
confidence: 99%
“…Our results indicated that 100 mM PDP solution (pH 7.4) containing L-arginine gave higher activity than 10 mM PDP solution (pH 7.4) with 100 mM L-arginine or 100 mM PDP solution (pH 7.4) without L-arginine in the refolding reaction. Since presence of L-arginine in the refolding reaction markedly increased the enzymatic activity, the reaction intermediates between ADI and L-arginine may be tightly bound by the combination of covalent links, polar interactions, or hydrophobic interactions [3,5].…”
Section: Discussionmentioning
confidence: 99%